2020
DOI: 10.3102/0162373720954183
|View full text |Cite
|
Sign up to set email alerts
|

Improving Preservice Teachers’ Feelings of Preparedness to Teach Through Recruitment of Instructionally Effective and Experienced Cooperating Teachers: A Randomized Experiment

Abstract: New studies show that the instructional effectiveness of preservice candidates and their cooperating teachers are positively related. However, we neither know if these relationships are causal nor, assuming they are, if it is possible to significantly increase the instructional effectiveness of the cooperating teacher pool. In this study, we randomly assign districts to receive recommendation lists (generated using administrative data) for the recruitment of more promising cooperating teachers. Districts recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…These findings suggest that human capital specific to grades and school types (e.g., curriculum and subject matter) may be more important for teacher candidate development than human capital specific to individual schools and districts (e.g., school/district culture and colleagues). But these conclusions are not universal, as for elementary math teachers, it appears that human capital specific to individual schools and districts is more important, which echoes findings on teacher evaluation ratings from Ronfeldt et al (2020). These findings have potentially important implications for the broader field of teacher preparation, though future research will need to disentangle the specific mechanisms that explain these relationships.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These findings suggest that human capital specific to grades and school types (e.g., curriculum and subject matter) may be more important for teacher candidate development than human capital specific to individual schools and districts (e.g., school/district culture and colleagues). But these conclusions are not universal, as for elementary math teachers, it appears that human capital specific to individual schools and districts is more important, which echoes findings on teacher evaluation ratings from Ronfeldt et al (2020). These findings have potentially important implications for the broader field of teacher preparation, though future research will need to disentangle the specific mechanisms that explain these relationships.…”
Section: Discussionmentioning
confidence: 90%
“…There is also evidence that the degree of selfreported (Boyd et al, 2009) and school-level (Goldhaber et al, 2017) alignment between student teaching and first jobs is predictive of future teacher effectiveness, as well as prior evidence from one TEP (Henry et al, 2013) that teaching in the same grade as student teaching is predictive of higher value added. Perhaps surprisingly, prior studies that consider matches between student teaching and first teaching positions in terms of school type (e.g., Ronfeldt, 2015) and the specific school (e.g., Goldhaber et al, 2017;Henry et al, 2013) have not found that these measures are predictive of teacher value added, though one recent study finds that same school hiring is predictive of higher teacher evaluation scores (Ronfeldt et al, 2020). To our knowledge, this is the first article to consider all of the measures of alignment discussed above, as well as measures of demographic alignment at the classroom level that have not been considered in prior analyses.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Specifically, both the effectiveness (as measured by value added) and instructional performance (as measured by inservice performance evaluations) of cooperating teachers have been found to be associated with the future effectiveness and instructional performance of their teacher candidates who themselves become teachers (Bastian et al, 2020; Goldhaber et al, 2020b; Matsko et al, 2020; Ronfeldt, Brockman, & Campbell, 2018; Ronfeldt, Matsko, et al, 2020). Three recent experimental studies build on this observational work by providing evidence that candidates randomly assigned to “better” student teacher placements (as proxied by cooperating teacher experience and value added and school value added) report better preparedness (Ronfeldt, Goldhaber, et al, 2018; Ronfeldt, Bardelli,et al, 2020) and receive better preservice clinical observation ratings (Goldhaber, Ronfeldt, Matsko et al, 2020) than candidates randomly assigned to “worse” placements.…”
Section: Background Literaturementioning
confidence: 99%
“…Mentees would then be able to apply different teaching methods and approaches, to establish cooperation with other mentors, and thus, to plan a lesson based on interdisciplinary approach to teaching. Furthermore, increasing the number of lessons affects the mentee's self-confidence and feeling of better preparedness for the teaching job (Ronfeldt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%